Weak Form of Efficiency in Nepal Stock Exchange - Joshi, Vishal; K.C., Kusum (KMC Research Journal, 2025)
Weak form of market efficiency asserts that historical stock price movements are already reflected in the current stock prices. Hence, historical stock prices do not have predictive power to estimate future stock prices. Due to contradictory empirical evidences, there is a need to re-explore the weak form of market efficiency. Market indices were selected by using judgmental sampling design covering the study period from 1st July 2020 to 28th April 2025. Based on descriptive and analytical research design, Jarque-Bera test, Kolmogor6ov-Smirnov test, Run test, Variance Ratio test, Augmented Dickey Fuller test and Phillips Perron test were used on daily and weekly returns of NEPSE and 12 sectoral indices to examine distribution patterns, random walk and stationarity. It was found that the daily returns series did not exhibit market efficiency while weekly returns exhibited mixed results. Hence, it is concluded that Nepalese stock market is not efficient in weak form on a daily basis. The findings of this study have immense implications for investors, academicians and regulatory authorities. Future researches can be conducted to explore semi-strong and strong form of market efficiency.